The Influence of Environmental Hypoxia on Hemostasis—A Systematic Review - Treml, Benedikt; Wallner, Bernd; Blank, Cornelia; Fries, Dietmar; Schobersberger, Wolfgang (Frontiers in Cardiovascular Medicine, 2022)
Humans have been ascending to high altitudes for centuries, with a growing number of professional- and leisure-related sojourns occurring in this millennium. A multitude of scientific reports on hemostatic disorders at high altitude suggest that hypoxia is an independent risk factor. However, no systematic analysis of the influence of environmental hypoxia on coagulation, fibrinolysis and platelet function has been performed. To fill this gap, we performed a systematic literature review, including only the data of healthy persons obtained during altitude exposure (<60 days). The results were stratified by the degree of hypoxia and sub-categorized into active and passive ascents and sojourns. Twenty-one studies including 501 participants were included in the final analysis. Since only one study provided relevant data, no conclusions regarding moderate altitudes (1,500–2,500 m) could be drawn. At high altitude (2,500–5,400 m), only small pathophysiological changes were seen, with a possible impact of increasing exercise loads. Elevated thrombin generation seems to be balanced by decreased platelet activation. Viscoelastic methods do not support increased thrombogenicity, with fibrinolysis being unaffected by high altitude. At extreme altitude (5,400–8,850 m), the limited data showed activation of coagulation in parallel with stimulation of fibrinolysis. Furthermore, multiple confounding variables at altitude, like training status, exercise load, fluid status and mental stress, prevent definitive conclusions being drawn on the impact of hypoxia on hemostasis. Thus, we cannot support the hypothesis that hypoxia triggers hypercoagulability and increases the risk of thromboembolic disorders, at least in healthy sojourners.